Preparation and Characterization of Hollow Glass Microspheres- Reinforced Poly (acrylonitrile-co-butadiene-co-styrene) Composites - Marina Panozzo Cunha; Ana Maria Colon Grisa; Jalma Klein; Matheus Poletto; Rosmary Nichele Brandalise (Materials Research, 2018)
In this study, poly(acrylonitrile-co-butadiene-co-styrene)/hollow glass microspheres (ABS/HGM) composites were prepared by means of a twin-screw extruder. HGM were incorporated at different loadings of 2.5, 5.0, and 7.5 wt.% at the central extruder zone with different types of ABS. The morphological, physical, thermal, rheological and mechanical properties of ABS/HGM composites were investigated. Statistical analysis reveals that high impact ABS addition is significant for improving composites’ impact strength. The results also indicated that addition of 5.0 wt.% of HGM along with 5.0 wt.% of powdery ABS at the central extruder zone maintains the HGM integrity while powdery ABS contributes to better filler dispersion in the matrix resulting in light-weight composites having improved mechanical properties.